Selective assembly of HIV-1 Vif-Cul5-ElonginB-ElonginC E3 ubiquitin ligase complex through a novel SOCS box and upstream cysteines - Yu, Yunkai (Cold Spring Harbor Laboratory Press, 2004)
APOBEC3G, which induces hypermutations in newly synthesized viral DNA, is suppressed by HIV-1 Vif, acting through Cul5-ElonginB-ElonginC E3 ubiquitin ligase. We have now characterized a novel SOCS box in HIV-1 Vif that mediates its interaction with ElonginC. In this SOCS box, alanine replaces the consensus cysteine in the previously identified SOCS box. This new motif was necessary but insufficient for interaction with Cul5-ElonginB-ElonginC, as two highly conserved Cys residues outside the SOCS box were required to interact with Cul5 but not ElonginC. Therefore, selective assembly with Cul5 versus Cul2 E3 may require protein interfaces besides the SOCS-box-ElonginC interaction.